2018
DOI: 10.1097/ogx.0000000000000588
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistent Weight Communication Among Prenatal Healthcare Providers and Patients: A Narrative Review

Abstract: Healthcare providers should counsel their pregnant patients on GWG with advice that is concordant with the Institute of Medicine Guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 63 publications
4
44
1
Order By: Relevance
“…Most HCPs agreed that the 5As gave them more knowledge and confidence to discuss GWG with their patients. The barriers to addressing GWG reported by the HCPs in this study were concordant with barriers reported in a recent narrative review, 24 in which HCPs perceived that GWG counseling may be ineffective or were uncertain whether their role involves GWG counseling. In this study, obstetricians indicated barriers such as competing medical issues more often than midwives, whereas midwives more frequently indicated worries about their patient becoming upset if GWG was discussed.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Most HCPs agreed that the 5As gave them more knowledge and confidence to discuss GWG with their patients. The barriers to addressing GWG reported by the HCPs in this study were concordant with barriers reported in a recent narrative review, 24 in which HCPs perceived that GWG counseling may be ineffective or were uncertain whether their role involves GWG counseling. In this study, obstetricians indicated barriers such as competing medical issues more often than midwives, whereas midwives more frequently indicated worries about their patient becoming upset if GWG was discussed.…”
Section: Discussionsupporting
confidence: 85%
“…Of note, study participants had a low prevalence of preexisting medical conditions, which, if present, might have taken precedence over GWG discussions. Although HCPs are considered one of the most reliable sources of prenatal information, 24 we found that women reported weight gain information through external sources such as the internet, friends, family, books, and/or previous personal experience. The use of such external sources may provide a reason as to why pregnant women may not be interested in initiating discussions of weight gain preemptively with their HCPs.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Studies have also shown that prenatal nutrition and related lifestyle counseling throughout gestation may lower GWG and neonatal macrosomia, especially in a high-risk population, such as women with overweight or obesity (Mitchell et al, 2017;Peccei et al, 2017). Hence, healthcare providers have the potential to influence and be a reliable source of evidence-based health information during an important period of a woman's life (Weeks et al, 2018). de Jersey et al (2018) found that a brief education session integrated into an existing mandatory training program has shown positive results in improving the knowledge and confidence of midwives in delivering advice and support for healthy GWG.…”
Section: Discussionmentioning
confidence: 99%